CASE STUDY EFFECTIVNESS OF AMYODARON USE IN PATIENTS WITH SUPRAVENTRICULAR TACHYCARDIA AND HYPOTHYROIDISM - Savitri, ,Ardyarini Dyah (UNUSA Press, 2019)
A woman, 53 years of age, with recurrent supraventricular tachycardia (SVT) with hypothyroidism was thought to be associated with amiodarone use. Patients repeatedly get amiodarone for their arrhythmias, where amiodarone has a broad antiarrhythmic effect making it effective for the management of SVT. In addition, the low inotropic properties of amiodarone are low, making amiodarone the drug of choice in patients with heart failure. However, repeated use of amiodarone can cause many side effects, one of which is amiodarone induced hypothyroidism (AIH). Patients are given thyroxine hormone substitution therapy during the use of amiodarone and the response to the therapy given is quite good, so the patient has a good prognosis.